PENGARUH LINGKUNGAN KERJA FISIK DAN NON FISIK TERHADAP PENINGKATAN KINERJA PEGAWAI DINAS PENDIDIKAN BONDOWOSO - Andri Desy Nurdiyanto; Heni Rosianti; Yunisar Bayu Kurniawan; Eka Martiana; Julaeha Evi Susanti; Sri Andayani; Hadyaningrum Hadyaningrum; Siti Mualfa; Sinung Sudrajad; Esa Rizqi Budisatya; Nurul Qomariah (Relawan Jurnal Indonesia, 2026)
This study analyzes the influence of physical and non-physical work environments on employee performance within government institutions and other organizations. The physical work environment, which includes aspects such as lighting, air circulation, cleanliness, temperature, and safety, is empirically tested and found to have a significant effect on improving employee comfort, health, and work productivity. Meanwhile, the non-physical work environment, measured through indicators such as supervision, work atmosphere, reward systems, sense of security, and fair treatment, is also proven to make an important contribution to employee motivation, loyalty, and performance optimization. The research method employed questionnaires and multiple linear regression statistical analysis involving respondents from various sectors. The findings indicate that both physical and non-physical work environment variables simultaneously and partially have a positive and significant effect on employee performance, with a contribution of variation exceeding 60% in performance improvement. These findings recommend that organizations pay greater attention to improving both physical and non-physical work environments to achieve optimal employee performance.